(untitled) (Research, Society and Development, 2021)
Leptospirosis a public health problem and an endemic zoonosis in Brazil, is diagnosed by serological methods. Therefore, low-cost and easy to execute methodologies with good/high sensitivity, such as Dot Blot, are an important diagnostic tool. The aim of this study was to standardize and validation the dot-blot technique for the serological diagnosis of bovine leptospirosis. Several concentrations of antigens applied to nitrocellulose membranes, and different dilutions of conjugated bovine serum were evaluated to develop and standardize the test. The best distinction/contrast between positive and negative samples was observed for 1μL antigen (0.11μg/μL outer membrane protein of the Hardjo serovar (OMPH) and 0.08 μg/μL outer membrane protein of the Wolffi serovar (OMPW)), 1:500 and 1:10000 bovine serum dilution and conjugate, respectively. The Dot Blot test efficiency was 71.87% and kappa index, 0.46 (p<0.0001). The other parameters measured were: sensitivity 91.89%; specificity 59.32%; positive predictive value 58.62%; and, negative predictive value 59.32%. In addition to high sensitivity, other advantages of the Dot Blot technique have been identified, such as practicality, low cost since it does not require sophisticated devices and the fact that the Hardjo and Wolffi OMP also reacted with serovars from other pathogenic serogroups. The results provided positive expectations for the use of Dot Blot as support in the diagnosis of bovine leptospirosis, especially if used as a screening test, stimulating further research for the future development of kits for diagnostic purposes.